2021
DOI: 10.1186/s12888-021-03621-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of circulating let-7b-5p with major depressive disorder: a nested case-control study

Abstract: Background Major depressive disorder (MDD) is one of the most common psychiatric disorders and is a great disease burden. However, its underlying pathophysiology and aetiology remain poorly understood. Available evidence suggests that circulating microRNAs (miRNAs) are associated with MDD, but it is still unknown whether miRNAs can predict subsequent incident MDD. Methods In this nested case-control study, a total of 104 individuals, who were free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Similar results were shown also in the hippocampus of the depressed mouse models 56 . However, one study on blood plasma of MDD subjects did not show any difference miR‐17‐5p expression 57 . Expression of miR‐4286 was studied in two brain regions, Brodmann area 24 of subjects with bipolar disorder died because of suicide, and Brodmann area 10 in suicides.…”
Section: Discussionmentioning
confidence: 52%
“…Similar results were shown also in the hippocampus of the depressed mouse models 56 . However, one study on blood plasma of MDD subjects did not show any difference miR‐17‐5p expression 57 . Expression of miR‐4286 was studied in two brain regions, Brodmann area 24 of subjects with bipolar disorder died because of suicide, and Brodmann area 10 in suicides.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, miRNA pair analysis confirmed the importance of miR-181c-5p expression combined with the expression levels of miR-338-3p or Let-7-5p in discriminating concussed from non-concussed players ( Figure 4 ). Interestingly, and of considerable diagnostic interest in the long-term development of brain degeneration, was the observation of a selective increase of a neurodegeneration-associated Let-7c-5p ( Figure 1A ), a chromosome-21q21-encoded miRNA also known to be specifically upregulated in Downs syndrome (trisomy 21) ( 67 , 68 ), AD ( 69 , 70 ) and depression ( 71 , 72 ). The selective upregulation of this specific miRNA may be related to and predictive for the initial triggering of brain damage and the onset of neurodegeneration characteristic of both acute and chronic brain injury as evidenced by TBI and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, this miRNA signature suggests long-lasting molecular changes potentially associated with pathological behaviors that could also be explored in follow-up longitudinal studies. The upregulation of the Let-7c-5p miRNA may be a useful biomarker related to and predictive of the initial triggering of brain damage and the onset of neurological deficits in acute and chronic neurodegeneration as evidenced by concussive brain injury, TBI, Down's syndrome, AD, and psychiatric disorders ( 67 72 ). At the same time, miR-17-5p and miR-22-3p may be useful biomarkers for persistent neuronal injury from mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…The most relevant considering statistical significance thresholds and longitudinal changes pre- and post-ECT treatment are miR-126, miR-106a, and miR-24. These 3 miRNAs have already been associated with depressive disorders, by evidence showing altered levels in peripheral blood samples of patients with MDD ( Camkurt et al, 2020 ; Maffioletti et al, 2021 ; Roumans et al, 2021 ). It seems that ECT treatment response is associated with a pattern of normalization of their expression in blood samples, which are altered by MDD in the pre-ECT period.…”
Section: Discussionmentioning
confidence: 99%